The Alkali-Tolerant Bacterium of Bacillus thuringiensis EM-A1 Can Effectively Perform Heterotrophic Nitrification and Aerobic Denitrification - Wang, Tingjiang; Chen, Mengping; Liang, Xiwen; Chen, Fali; He, Tengxia; Li, Zhu (Frontiers in Environmental Science, 2022)
Removal of nitrogen from hydroxylamine could effectively improve wastewater treatment efficiency. In this work, Bacillus thuringiensis EM-A1 was obtained from a biogas digester with hydroxylamine as the only nitrogen source. Hydroxylamine (100%) and total nitrogen (71.86%) were efficiently removed under the following conditions: 30 ℃, sucrose as carbon source, carbon: nitrogen ratio 40, rotation speed 0 rpm, pH 9.58 and inoculant concentration of 0.58×108 colony-forming units. Ammonium was completely consumed by strain EM-A1 and 8.32±0.08 mg/L of nitrate was produced during the ammonium removal process. During aerobic denitrification, the removal efficiencies of NO2-N and NO3-N by strain EM-A1 were 100% and 76.67%, respectively. There were about 29.34%±0.18%, 26.71±0.36% and 23.72±0.88% initial total nitrogen lost as nitrogenous gas when NH4+, NO3− and NO2− were separately used as the s ole nitrogen source. The specific activities of ammonia monooxygenase, hydroxylamine oxidoreductase, nitrate reductase and nitrite oxidoreductase were successfully detected as 0.37, 0.88, 0.45 and 0.70 U/mg protein, respectively. The abovementioned results indicated that B. thuringiensis EM-A1 is a promising candidate for bioremediation of inorganic nitrogen from wastewater.